REGENERATING CODETECHNIQUE IN DISTRIBUTED STORAGE - Agus Maman Abadi; Karyati Karyati; Musthofa Musthofa; Emut Emut (Jurnal Sains Dasar, 2016)
Abstract The Increasing need of storing large amounts of data presents a new challenge. One way to address this challenge is to use distributed data storage system. One of the strategies implemented in the distributed data storage system is using the technique of regenerating code. The code used in this technique is based on the algebraic structure of fields. Some studies have also been carried out to create code that is based on the other algebraic structure namely module. In this study, we attempted to assess the implementation of the code module at regenerating technique code. The study showed there is a potential properties code based on module that can be used in regenerating code technique. Keywords: Distributed storage, regenerating code technique, module code